Juvenile Probationers, Restitution Payments, and Empathy: An Evaluation of a Restorative Justice Based Program in Northeastern Pennsylvania - Kuehn, Sarah; Yarnell, John; Champion, David R. (International Journal of Criminology and Sociology, 2014)
Restitution programs are widely used to hold offenders accountable for their actions while providing restoration to victims and community service. However, compliance with restitution requirements is a major problem, as reported by juvenile probation offices across the country. The Firewood Program was developed for juvenile probationers in a rural Pennsylvania county to improve the completion rate of restitution payments to victims and provide community service. This study examines the effectiveness of the restitution program, which was measured as an increase in the offender’s level of empathy and shorter completion times of restitution payments.